Psychological Behavior of Frontline Medical Staff in the Use of Preventive Medication for COVID-19: A Cross-Sectional Study - Yu, Xiaoyan; Li, Yuxi; Tang, Li; Deng, Lu; Zhao, Yuxin; Zhao, Xianmei; Xu, Huilan; Zeng, Ming (Frontiers in Psychology, 2020)
ABSTRACT Purpose: to understand the current situation and psychological analysis of the use of self-prevention Medicine about Psychological behavior on medical staff in fighting against COVID-19. Methods: A total of 290 medical staff in fighting against COVID-19 was investigated by filling out Generalized Anxiety Disorder Scale (GAD-7) and a questionnaire was applied to investigate their Psychological behavior of self-prevention Medicine, from 10 January to 10 March 2020. Results: Among the surveyed front-line medical personnel, 77.6% used self-prophylactic Medicine. The proportions of routine prophylactic Medicine, Medicine in suspected infection and Medicine in occupational exposure were 47.6%, 40.9% and 11.6% respectively. The scores of anxiety scale on different preventive medication frequencies were statistically significant (P < 0.05). Compared with other groups, the scores of anxiety scale on special occupational exposure (exposure to respiratory pathogen and blood borne pathogens) were statistically significant. The proportions of front-line medical personnel choosing western medicine, traditional Chinese medicine and integrated traditional and western medicine for preventive COVID-19 were 24.4%, 28.0% and 47.6%. There were statistical differences in the scores of anxiety scale of different medication types (P < 0.05 ) , and the difference also has the statistically significant between the western medicine group and other groups. Conclusion: The anxiety level of people who take medicine during occupational exposure is higher. Compared with the persons who use the western medicine, the combination of Chinese and western medicine may relieve the anxiety of front-line medical staff.